Evaluation of nuclear knowledge management: an outcome in JAERI. (14th July 2006) - Yanagisawa, Kazuaki
The author performed an ex post evaluation on the nuclear research of JAERI and revealed that the national funds invested in this field were 4 b$. With aid of NKM, it was revealed that the total outcome was 6 b$, where the creation of nuclear markets for electricity and nuclear facilities was the main stream. This implies that the cost benefit effect is 6 b$/4 b$ = 1.5 (>1). From this, it can be concluded that JAERI contributes not only to technological promotion of nuclear activity but also to the increase of gross domestic product (GDP).